Emulsifying Properties of Dried Soy-Whey, Dried Tofu-Whey, and Their Isolated Proteins - Sobral Pablo A.; Ossa J. Sebastian Henao; Palazolo Gonzalo G.; Wagner Jorge R. (Polish Journal of Food and Nutrition Sciences)
This paper focuses on the comparative study of emulsifying properties of dried tofu-whey, dried soy-whey and their isolated proteins. Oil-in-water emulsions were prepared at equivalent protein concentration (0.1, 0.5 and 1.0 g/100 mL), using sunflower oil as lipid phase (oil mass fraction = 0.33). Tofu-whey and soy-whey were dehydrated by freeze-drying (LTW and LSW, respectively) or thermal-drying (DTW and DSW, respectively). Moreover, a heated LSW sample in anhydrous condition (h-LSW) was included. The emulsion formation and stability at rest was evaluated using a vertical scan analyzer, according to multiple light scattering theory, particle size and oiling off measurements. Even though the stability to gravitational separation and coalescence increased with increasing protein concentration, freeze-dried whey samples exhibited a higher ability to form and stabilize emulsions respect to that of thermally-dried ones, especially for those obtained from soy-whey. Moreover, h-LSW emulsions were more stable than that of LSW sample presumably due to protein glycosylation. The global emulsion stability decreased in the order: LTW>DTW>h-LSW>LSW>DSW. Moreover, at equivalent protein concentration in the continuous phase, the isolation of proteins from lyophilized whey-samples by treatment with cold acetone (LTW-P, LSW-P and h-LSW-P, respectively) improved their emulsifying properties. Again, this improvement was more pronounced for samples obtained from soy-whey, probably due to partial protein denaturation associated to treatment with the organic solvent. In conclusion, this paper should be considered as basis for further studies concerned with the potential application of soy-whey and tofu-whey proteins as emulsifiers in different systems.